Trichoderma harzianum inoculation promotes sweet sorghum growth in the saline soil by modulating rhizosphere available nutrients and bacterial community - Wei, Yanli; Yang, Han; Hu, Jindong; Li, Hongmei; Zhao, Zhongjuan; Wu, Yuanzheng; Li, Jishun; Zhou, Yi; Yang, Kai; Yang, Hetong (Frontiers in Plant Science, 2023)
As one of the major abiotic stresses, salinity can affect crop growth and plant productivity in the worldwide. The inoculation of rhizosphere or endophytic microorganisms can enhance plant tolerance to salt stresses, while the potential mechanism is not clear. In this study, Trichoderma harzianum ST02 was applied on sweet sorghum [Sorghum bicolor (L.) Moench] in a field trial to investigate the effects on microbiome community and physiochemical properties in the rhizosphere soil. Compared to the non-inoculated control, Trichoderma inoculation significantly increased the stem yield, plant height, stem diameter and total sugar content in stem by 35.52%, 32.68%, 32.09% and 36.82%, respectively. In addition, Trichoderma inoculation improved the nutrients availability (e.g. N, P and K) and organic matter in the rhizosphere soil, and changed bacterial community structure and function in both bulk and rhizosphere soil by particularly increasing the relative abundance of Actinobacter and N-cycling genes (nifH, archaeal and bacterial amoA). We proposed that T. harzianum ST02 could promote sweet sorghum growth under saline condition by regulating available nutrients and bacterial community in the rhizosphere soil.